Pengaruh Sebaran Konsentrasi Klorofil-a Berdasarkan Citra Satelit terhadap Hasil Tangkapan Ikan Tongkol (Euthynnus sp) Di Perairan Selat Bali - I Made Satya Prayoga; I Dewa Nyoman Nurweda Putra; I Gusti Ngurah Putra Dirgayusa (Fakultas Kelautan dan Perikanan Universitas Udayana, 2017)
One of fisheries potential in Bali Strait is tuna fish (Euthynnus sp). Tuna fish (Euthynnus sp) resources is highly influenced by waters productivity which indicated by the chlorophyll-a concentration distribution. The aims of this study are: to find out the concentration spatial of chlorophyll-a distribution in Bali strait, to find out temporal variability of chlorophyll-a and tuna fish (Euthynnus sp) in Bali strait, and to find out the influence of chlorophyll-a concentration distribution to the catch of tuna fish (Euthynnus sp) in Bali strait. The analysis of the influence of chlorophyll-a concentration distribution to the catch of tuna fish (Euthynnus sp) in Bali strait uses regression polynomial order 2, correlation, and cross correlation. The influence of chlorophyll-a concentration distribution to the catch of tuna fish (Euthynnus sp) in Bali strait yearly time series climatology amounted to R2 = 0,1624 or 16,24%, the correlation coefficient values obtained by r = 0,1889. Seasonal time series climatology in west season (December - February) R2 = 0,0707 or 7,07%, the correlation coefficient values obtained by r = 0,0749. The transitional season 1 (March - May) R2 = 0,0095 or 0,95%, the correlation coefficient values obtained by r = - 0,0092. The east season (June - August) R2 = 0,086 or 8,6%, the correlation coefficient values obtained by r = - 0,2155. The transitional season 2 (September - November) R2 = 0,0482 or 4,82%. The correlation coefficient values obtained by r = - 0,1805